The Effect of Self-Esteem on the Development of Narcissistic Behavior Among Students Engaged in Social Media - Hafni, Merri (Kuras Institute, 2025)
The increasing prevalence of social media usage among university students has raised significant concerns about its psychological effects, particularly in relation to self-esteem and the development of narcissistic behavior. As students spend more time engaging with social media platforms, behaviors such as seeking validation through